Transcribe this way: Rap1 confers promoter directionality by repressing divergent transcription. Issue 3 (27th May 2019) - Wu, Andrew C.K.; Van Werven, Folkert J.
ABSTRACT: In eukaryotes, divergent transcription is a major source of noncoding RNAs. Recent studies have uncovered that in yeast, the transcription factor Rap1 restricts transcription in the divergent direction and thereby controls promoter directionality. Here, we summarize these findings, propose regulatory principles, and discuss the implications for eukaryotic gene regulation.